2009
DOI: 10.1111/j.1469-8749.2009.03316.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring changes and predicting loss of ambulation in Duchenne muscular dystrophy with the Motor Function Measure

Abstract: D1Dimension 1 METHOD Three studies were performed. Two studies included only physiotherapy-treated patients, with 13 patients (males mean age 11y 7mo, SD 1y 10mo, range 8-14y) in the 3-month study and 41 patients (males mean age 14y 1mo, SD 5y 5mo, range 6-32y) in the 1-year study. A third study compared 12 patients treated with steroids with 12 age-and motor-function-matched untreated patients (males mean age of treated patients 10y 2mo, SD 2y 2mo range 6-14) over a 12-month period.RESULTS Over 3 months, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
0
25

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(140 citation statements)
references
References 15 publications
8
107
0
25
Order By: Relevance
“…(15,16) The GMFM assesses the gross motor abilities of children with CP and MFM of children with neuromuscular diseases. The scores of both scales were transformed into a percentage of the maximum score, and these percentages were analyzed together as a representation of motor function.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…(15,16) The GMFM assesses the gross motor abilities of children with CP and MFM of children with neuromuscular diseases. The scores of both scales were transformed into a percentage of the maximum score, and these percentages were analyzed together as a representation of motor function.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Studies have shown the relevance of motor function follow up to monitor DMD accurately 2,3,4 . Global motor scales should be complemented by functional tasks assessment because, despite the continued decline in muscle strength, children with DMD continue to perform the activities using compensatory movements 5,6 . The analysis of compensatory movements employed during functional activities shows the changes in muscular synergies.…”
mentioning
confidence: 99%
“…For instance, Vuillerot et al 30 showed that the MFM was useful to detect mobility loss and functional dependence increase. It predicted gait loss within a year, when Dimension 1 was 40% or lower 30 . Conversely, Bakker et al 26 showed that MRC provided good references for DMD prognosis.…”
Section: Bartels Et Almentioning
confidence: 99%